Circular economy implemented on the construction site - Elżbieta Szafranko (Budownictwo o Zoptymalizowanym Potencjale Energetycznym, 2025)
Construction is a branch of the economy that occupies a leading place in waste production. The problem concerns both the demolition of buildings at the end of their lifespan and the construction process itself. During the demolition process, waste is segregated, and most often concrete and brick rubble, wooden and wood-based elements, and metal and glass are recycled. However, there is still a large amount of mixed waste, which often contains hazardous waste. It is necessary to store this waste safely. Another problem is waste generated during construction. The largest percentage of which is packaging. In construction practice, the waste is most often transported to companies that deal with its segregation and partial processing as mixed waste. However, in the idea of a closed-loop economy, in addition to waste processing, there is an attempt to reduce the negative impact on the environment which may be caused by, among other factors, the transport of this waste. The article proposes the possibility of using some packaging waste directly on the construction site. In the article, the authors proposed a practical solution to manage a significant part of the waste generated during construction. This solution provides a place for the production of elements needed to develop the area around the building using technology based on secondary raw materials. This approach allows for the implementation of the green building philosophy in a more complete form.